2006
DOI: 10.1002/ejoc.200600413
|View full text |Cite
|
Sign up to set email alerts
|

Functional Group Migration in Reactions of 1,2‐Diferrocenyl‐3‐(methylthio)cyclopropenylium Iodide with CH Acids

Abstract: 1,2‐Diferrocenyl‐3‐(methylthio)cyclopropenylium iodide reacts with malonic acid derivatives (diethyl malonate and malononitrile as the active methylene compounds) to give mainly the corresponding 3,4‐diferrocenyl‐2‐(methylthio)hexa‐2,4‐dienedioic acid and 2,3‐diferrocenyl‐4‐(methylthio)buta‐1,3‐diene‐1,1‐dicarboxylic acid derivatives as well as ethyl 2,3‐diferrocenyl‐4‐(methylthio)‐5‐oxocyclo‐1,3‐pentadiene‐1‐carboxylate or 2‐cyano‐3,4‐diferrocenyl‐5‐(methylthio)‐2,4‐cyclopentadien‐1‐imine. X‐ray diffraction d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The transformations of vinylcarbenes (12a-c) with intramolecular proton shift affords ultimately the linear products 10a-c. The intramolecular character of the transformation of analogous vinylcarbenes was proved earlier for the reaction of the cation 5c with diethyl [D 2 ]malonate [15].…”
Section: Resultsmentioning
confidence: 93%
“…The transformations of vinylcarbenes (12a-c) with intramolecular proton shift affords ultimately the linear products 10a-c. The intramolecular character of the transformation of analogous vinylcarbenes was proved earlier for the reaction of the cation 5c with diethyl [D 2 ]malonate [15].…”
Section: Resultsmentioning
confidence: 93%
“…1,3-Dicarbonyl compounds (1a-f) react with 1-morpholino-(or 1-piperidino-)-2,3-diferrocenylcyclopropenilyum terafluoroborates as described earlier [14,15] to afford 3-[acyl-(ethoxycarbonyl)]methylidene-1,2-diferrocenylcyclopropenes and 3-diacylmethylidene-1,2-diferrocenylcyclopropenes (2a-f) in 55-65 % yield; these compounds are used as starting compounds (Scheme 2). Scheme 2. We found that diferrocenylcyclopropene 2a reacts with hydrazine in boiling ethanol to afford regioselectively only one reaction product, methylpyridazine 3a (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…90%. Ethyl ( E ) ‐ 2‐ferrocenylmethylidene(benzoyl)acetate ( 1 ) and ‐( p ‐nitrobenzoyl)acetate ( 2 ), ethyl E‐ and Z ‐ 2‐ferrocenylmethylideneacetoacetates ( 3a ) and ( 3b ) were prepared by condensation of ferrocenecarbaldehyde with ethyl benzoyl‐, p ‐nitrobenzoyl‐, and acetoacetates 4a , 4b , 4c , respectively, in benzene in the presence of piperidinium acetate [20, 21, 26, 27]. The physical and 1 H‐NMR spectroscopic characteristics of compounds 1 , 3a , and 3b were in accord with the literature data [20, 21, 26, 27].…”
Section: Methodsmentioning
confidence: 99%